A Mini Review on Non-augmentative Surgical Therapy of Peri-Implantitis—What Is Known and What Are the Future Challenges? - Bertl, Kristina; Stavropoulos, Andreas (Frontiers in Dental Medicine, 2021)
Non-augmentative surgical therapy of peri-implantitis is indicated for cases with primarily horizontal bone loss or wide defects with limited potential for bone regeneration and/or re-osseointegration. This treatment approach includes a variety of different techniques (e.g., open flap debridement, resection of peri-implant mucosa, apically positioned flaps, bone re-contouring, implantoplasty, etc.) and various relevant aspects should be considered during treatment planning. The present mini review provides an overview on what is known for the following components of non-augmentative surgical treatment of peri-implantitis and on potential future research challenges: 1) decontamination of the implant surface, 2) need of implantoplasty, 3) prescription of antibiotics, and 4) extent of resective measures.